2017
DOI: 10.1111/ojoa.12122
|View full text |Cite
|
Sign up to set email alerts
|

Fields, Ritual and Religion: Holistic Approaches to the Rural Landscape in Long‐Term Perspective (c.1500 BC–AD 1086)

Abstract: Summary This paper discusses the relationship between agricultural activity and ritualized/religious practices in England from the middle Bronze Age to the early medieval period (c.1500 BC–AD 1086). It is written in the context of the ERC‐funded, Oxford‐based ‘English Landscapes and Identities project’ (EngLaId), which involved the compilation of an extensive spatial database of archaeological ‘monuments’, finds and other related data to chart change and continuity during this period. Drawing on this database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The Yorkshire Wolds dyke systems appear to have had a long history of development from the Late Bronze Age to the Late Iron Age or beyond (Dent, 1984;Giles, 2012), without major disruption to the landscape organisation. Pit alignments are also found on the Yorkshire Wolds as cropmarks; the associated banks survive in places on the North York Moors, for example on the Tabular Hills (Spratt, 1988). When these features are excavated, they usually appear to be associated with 'prehistoric' activity, though Romano-British examples are also known.…”
Section: The Study Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yorkshire Wolds dyke systems appear to have had a long history of development from the Late Bronze Age to the Late Iron Age or beyond (Dent, 1984;Giles, 2012), without major disruption to the landscape organisation. Pit alignments are also found on the Yorkshire Wolds as cropmarks; the associated banks survive in places on the North York Moors, for example on the Tabular Hills (Spratt, 1988). When these features are excavated, they usually appear to be associated with 'prehistoric' activity, though Romano-British examples are also known.…”
Section: The Study Regionmentioning
confidence: 99%
“…Subsequent archaeological work has refined our knowledge of the extent and character of land divisions of all ages (e.g. Bradley, 1977; Fleming, 1988; Yates, 2007; Oosthuizen, 2013; Rippon et al, 2015; Ten Harkel et al ., 2017). Yet, despite their common occurrence and importance, the timing and tempo of their emergence and expansion is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Van Giffen 1939, 88; Brongers 1976, 20; Cooper 2016, 303–5; Ten Harkel et al . 2017, 418) – suggested that they might have played a part in funerary rituals (Janssen 1848, 122; Brongers 1976, 23; Van der Sanden 2009, 17), as he found no evidence for their use as settlements, garden plots, or sheep-pens (Janssen 1848, 121–2).
Fig. 2Schematic plans of several Dutch Celtic fields.
…”
Section: The Deep Roots Of Dutch Celtic Field Studiesmentioning
confidence: 99%
“…Ten Harkel et al . 2017, 420)? One could argue that it is mere chance that none of these has, as yet, been identified (given the few sites investigated and small areas uncovered in such excavations; but see Fig.…”
Section: Implications: the Netherlands’ Most Stable Agricultural Landmentioning
confidence: 99%
See 1 more Smart Citation